2016
DOI: 10.15184/aqy.2016.193
|View full text |Cite
|
Sign up to set email alerts
|

The ‘People of the British Isles’ project and Viking settlement in England

Abstract: The recently concluded ‘People of the British Isles’ project (hereafter PoBI) combined large-scale, local DNA sampling with innovative data analysis to generate a survey of the genetic structure of Britain in unprecedented detail; the results were presented by Leslie and colleagues in 2015. Comparing clusters of genetic variation within Britain with DNA samples from Continental Europe, the study elucidated past immigration events via the identification and dating of historic admixture episodes (the interbreedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…It shows a high density of contemporary Scandinavian metalwork items [ 3 ], and high proportions of Scandinavian major and minor place names [ 2 ]. This pervasive Scandinavian cultural influence has been argued to indicate the impact of substantial numbers of Viking settlers [ 4 ], not just local cultural shift under an incoming elite. Despite its name, the Danelaw presents good evidence of a variety of Scandinavian influences, not restricted to the modern category of Danes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It shows a high density of contemporary Scandinavian metalwork items [ 3 ], and high proportions of Scandinavian major and minor place names [ 2 ]. This pervasive Scandinavian cultural influence has been argued to indicate the impact of substantial numbers of Viking settlers [ 4 ], not just local cultural shift under an incoming elite. Despite its name, the Danelaw presents good evidence of a variety of Scandinavian influences, not restricted to the modern category of Danes.…”
Section: Introductionmentioning
confidence: 99%
“…The cluster’s estimated ~35% ancestry from north-west Germany was ascribed to earlier ‘Saxon’ migrations. This interpretation has been challenged [ 4 ], partly on the grounds that north-west German contributions may equally reflect Danish Viking influence; in this view, the lack of a ‘Danelaw signal’ could result from free migration within lowland Britain over the last millennium. A similar SNP-based study of Ireland [ 10 ] indicated a major influence from northern Europe and Scandinavia, particularly in eastern Ireland, interpreted as a Norse Viking contribution and compatible with attested patterns of settlement, including the Viking foundation of Dublin.…”
Section: Introductionmentioning
confidence: 99%
“…The nature and magnitude of Scandinavian migrations to England in the early medieval period is still disputed (e.g. Sawyer 1957; Hadley 2006; Leslie et al 2015; Kershaw & Røyrvik 2016). The size and nature of Great Army winter camps has been used as a proxy to estimate the size of the invading forces, but with divergent results (cf.…”
Section: Introductionmentioning
confidence: 99%
“…This may incur chance findings due to inherent population differences. The Danish and British had mingled ancestries since the eighth century and Denmark presented greater genetic affinity with Great Britain than her neighboring Scandinavian countries and Germany 44 , 45 . With population admixture, differences in the two populations could have attenuated.…”
Section: Discussionmentioning
confidence: 99%